2023
DOI: 10.1038/s41467-023-42474-1
|View full text |Cite
|
Sign up to set email alerts
|

Phase separation of BuGZ regulates gut regeneration and aging through interaction with m6A regulators

Qiaoqiao Zhang,
Kai Deng,
Mengyou Liu
et al.

Abstract: Exploring the role of phase separation in intracellular compartment formation is an active area of research. However, the associations of phase separation with intestinal stem cell (ISC)-dependent regeneration and aging remain unclear. Here, we demonstrate that BuGZ, a coacervating mitotic effector, shows age- and injury-associated condensation in Drosophila ISC nuclei during interphase. BuGZ condensation promotes ISC proliferation, affecting Drosophila gut repair and longevity. Moreover, m6A reader YT521-B ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…Another open question concerns the maintenance of oxidation processes in the reductive cytosol. In recent studies, LLPS has gained attention as a new principle of subcellular organization 21,47,48 . For gephyrin it was recently demonstrated that it forms liquid droplets in the presence of a multimeric receptor model 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Another open question concerns the maintenance of oxidation processes in the reductive cytosol. In recent studies, LLPS has gained attention as a new principle of subcellular organization 21,47,48 . For gephyrin it was recently demonstrated that it forms liquid droplets in the presence of a multimeric receptor model 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite IDPs being often poorly conserved ( 42 , 43 ), SUF4 shares substantial homology with the animal protein BuGZ. In these organisms, BuGZ plays essential roles in both mitotic and transcriptional regulation by interacting with various cellular machineries, including the spindle assembly checkpoint protein (SAC) Bub3, the spliceosome, and epigenetic factors ( 13 , 14 , 44 ). While SUF4’s primary function in plants revolves around regulating flowering time, recent research has unveiled its potential involvement in analogous mitotic and transcriptional regulatory processes ( 4547 ).These newfound roles raise a series of questions, including whether SUF4’s phase separation has evolved distinct functionality specific to plant flowering or if it serves as a universal mechanism within eukaryotic systems.…”
Section: Discussionmentioning
confidence: 99%
“…SUF4 is an ortholog of the animal protein BuGZ (Supplemental Figure 3), an IDP initially found to undergo temperature-dependent phase separation in vitro and regulate spindle assembly in vivo (13)(14)(15). Therefore, to assess the potential for SUF4 to undergo phase separation independently of any plant cell factors, we expressed and purified 6xHis-mVenus-SUF4 (isoform 1, WT) from SF9 insect cells.…”
Section: Suf4 Phase Separates In Vitromentioning
confidence: 99%
See 1 more Smart Citation
“…The overexpression of ZNF207 has been significantly associated with poor clinical outcomes in liver malignancies. Previous studies revealed the involvement of ZNF207 in the modulation of stem cell self-renewal and pluripotency, as well as its influence on chromosome arrangement. ,, Inhibiting ZNF207 affects the BUB3 mitotic checkpoint protein (BUB3) and BUB1 mitotic checkpoint serine/threonine kinase (BUB1) kinetochore localization, causing defects in spindle formation in GSCs and other transformed cells but not in human neural stem cells or nontransformed ones. Moreover, it has been observed that in p53-deficient CSCs, targeting ZNF207 might enhance the sensitivity of tumor cells to cisplatin by inhibiting spindle assembly checkpoints .…”
Section: Introductionmentioning
confidence: 99%